Description of Erythrocyte, Leucocite and Growth Performance of Green Catfish (Hemibagrus nemurus) Feeded With Addtion of Commercial Bread (Saccharomyces cerevisiae) - Rizal Akbar Hutagalung (Airlangga University, 2020)
Baung fish (Hemibagrus nemurus) is a freshwater fish species native to Indonesian public waters, particularly in Sumatra and Kalimantan. Baung fish has thick, soft meat, delicious taste, and has high economic value. This research was conducted at the Workshop for Fisheries Cultivation Technology Study Program, using a container in the form of a fiber tub which is divided into 4 parts (100cm x 50cm x 7 cm) using waring. The test organism was fish baung with fish size 5cm-7cm, which were spread as many as 10 fish/bulkhead and kept for 60 days. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. The treatment used was the addition of S. cerevisiae yeast to artificial feed (pellets) with different doses. Where the control treatment (K): without the addition of S. cerevisiae, treatment A (P1): with a dose of S. cerevisiae 0.2%, treatment B (P2): addition of S. cerevisiae by 0.5%, and treatment C (P3 ): S. cerevisiae dose of 0.8%. Application of S. cerevisiae uses a coating method with a frequency of 2 times a day. The parameters observed included fish health status (total red blood cells and white blood cells, hematocrit, hemoglobin, and blood glucose) as well as production parameters such as absolute growth, daily growth rate, total feed consumption, feed conversion ratio, survival rate. The results showed that the absolute growth rate and the highest daily growth rate were found in treatment (P2), respectively 21.86 ± 10.05 grams and 0.86 ± 0.38%. On the other hand, the lowest FCR value was found in treatment (P3), namely 1: 1.25 ± 0.60. This shows that the provision of S. cerevisiae has a positive impact on increasing red blood cells, white blood cells, and the growth performance of the fish. Keywords: Erythrocytes, Leukocytes, Growth, Hemibagrus nemurus